NON-SUICIDAL SELF INJURY (NSSI) IN ADOLESCENTS: DILEMMA IN DIAGNOSIS OF A CASE - Iftikhar, Maryam (Journal of Arts & Social Sciences, 2022)
Non-suicidal self-injurious behaviors are getting prevalent in third world countries especially in Pakistan. This case report describes a typical case of Non-suicidal self-injurious behaviors in a young female (most vulnerable population) with symptoms of cutting different body parts that she mimic from other friends. The difference in intention and gains of both the behaviors can helps in diagnosing and treatment, preventing invasive medicinal and psychological treatments, reserving available healthcare resources. Similar cognitive, emotional, psychological and behavioral factors underlie and perpetuate non-suicidal self-injury and emotional disorders. This brief case report aims to explain the dilemma of identifying the case and to target emotional disorders in treating comorbid borderline personality traits.